Minat Konsumen Terhadap Bunga Potong Krisan Di Kelurahan Kakaskasen II Kecamatan Tomohon Utara Kota Tomohon - Wijayanti, Puput; Tambas, Jane Sulinda; Tarore, Melissa Lady Gisela (Sam Ratulangi University, 2023)
This study aims to determine and describe consumer interest in chrysanthemum flowers sold on Flovist OLV and Florist CL in Kakaskasen II sub-district of Tomohon Temohon Town of Tomohon. This research was implemented for 2 months, from July to August 2022. The data used in this study were primary data and secondary data. Primary data is obtained from direct interviews with consumers who buy interest. Secondary data was obtained from Kakaskasen II's kelurahan office and the owner of Florist. In this study the number of respondents as many as 16 people with the accidental sampling method, that is by taking the respondents who are buying interest. The data analysis method is a qualitative descriptive analysis. Based on the research it could be concluded that consumer interest in chrysanthemum cut flowers in kakaskasen ii district of tomohon north of the city of tomohon. The chrysanthemum cut flower has a pretty good interest in the consumer, especially in the color, shape, and price of flowers. Chrysanthemum cut flowers are said to be an everyday consumer consumption, since every day it is bought for chrysanthemum flowers to be carried by the grave.